Gene therapy decreases seizures in a model of Incontinentia pigmenti. Issue 1 (July 2017) - Dogbevia, Godwin K.; Töllner, Kathrin; Körbelin, Jakob; Bröer, Sonja; Ridder, Dirk A.; Grasshoff, Hanna; Brandt, Claudia; Wenzel, Jan; Straub, Beate K.; Trepel, Martin; Löscher, Wolfgang; Schwaninger, Markus
Abstract : Objective: Incontinentia pigmenti (IP) is a genetic disease leading to severe neurological symptoms, such as epileptic seizures, but no specific treatment is available. IP is caused by pathogenic variants that inactivate the Nemo gene. Replacing Nemo through gene therapy might provide therapeutic benefits. Methods: In a mouse model of IP, we administered a single intravenous dose of the adeno‐associated virus (AAV) vector, AAV‐BR1‐CAG‐NEMO, delivering the Nemo gene to the brain endothelium. Spontaneous epileptic seizures and the integrity of the blood–brain barrier (BBB) were monitored. Results: The endothelium‐targeted gene therapy improved the integrity of the BBB. In parallel, it reduced the incidence of seizures and delayed their occurrence. Neonate mice intravenously injected with the AAV‐BR1‐CAG‐NEMO vector developed no hepatocellular carcinoma or other major adverse effects 11 months after vector injection, demonstrating that the vector has a favorable safety profile. Interpretation: The data show that the BBB is a target of antiepileptic treatment and, more specifically, provide evidence for the therapeutic benefit of a brain endothelial‐targeted gene therapy in IP. Ann Neurol 2017;82:93–104